Fuzzy Quantification System untuk Menganalisis Pengaruh Minat, Motivasi Belajar dan Tingkat Kehadiran Siswa terhadap Prestasi Belajar di SMA Muhammadiyah 1 Purwokerto - Ridho Muktiadi; Septian Ari Wibowo; Windaru Windaru (Department of Informatics Engineering, Universitas Muhammadiyah Purwokerto, 2013)
One of benchmarks to know the capabilities a person is through grades of their studies. Grades can be affected by various factors, such as interest, motivation and attendance. This research aims to analyze the effect of interests, motivation and attendance levels on learning achievement in students of SMA Muhammadiyah 1 Purwokerto, by using Fuzzy Quantification Theory I to explains qualitative value such as interest and motivation in the form of questionnaires filled in range of value [0 1]. The results of this research shows that there are effects between indicators, that is responsive study is an indicator with the highest contribution to the achievement of study, with the presence of more than 128. Contribution value to indicator of responsive learning is 40.8885 μ [x] to the weight category at 72.2419 μ [x] that influence student achievement (final grade). And there is influence of indicator of learning motivation, which is the indicator shows the high interest that provide additional contributions on learning achievement with the highest attendance of over 129. Contributions of an indicator high interest valued 40.8404μ[x] to the weight category of 72.1938μ[x] that influence student achievement